Dual-Beam Scanning Electron Microscope (SEM) and Focused Ion Beam (FIB): A Practical Method for Characterization of Small Cultural Heritage Objects. Issue 1656 (15th September 2014) - Carl, Matthew; Smith, Chris A.; Young, Marcus L.
ABSTRACT: Knowledge of the composition of many cultural heritage objects is limited, resulting in many unanswered questions in regards to the provenance, composition, and production methods. In this paper, our objective is to show that dual beam scanning electron microscope (SEM) and focused ion beam (FIB) can be used rapidly and non-destructively to determine the surface and bulk metal compositions in small cultural heritage objects. We show, for the first time, that this novel FIB technique can be successfully applied non-destructively to cultural heritage objects by examining three representative silver plated objects (Candelabra, "Century" spoon, and New York World's Fair spoon) from the Dallas Museum of Art's unparalleled collection of modern American silver. In each case, we successfully reveal and characterize the bulk metal as well as the Ag-plating, up to ∼80 µm deep and show that there is no visual damage resulting from the milling process of the FIB. This novel characterization technique can be applied, due to its ease of availability and rapid use, to many other problems in addition to silver plated objects, making dual beam SEM/FIB a possible cornerstone technique in the study of cultural heritage objects.